Inhibitory receptor CD47 binding to plasma TSP1 suppresses NK-cell IFN-γ production via activating the JAK/STAT3 pathway during HIV infection - Lang, Bin; Wang, Meiting; Zhang, Zining; Fu, Yajing; Han, Xiaoxu; Hu, Qinghai; Ding, Haibo; Shang, Hong; Jiang, Yongjun (Journal of translational medicine, 2023)
Natural killer (NK) cells play an important first-line role against tumour and viral infections and are regulated by inhibitory receptor expression. Among these inhibitory receptors, the expression, function, and mechanism of cluster of differentiation 47 (CD47) on NK cells during human immunodeficiency virus (HIV) infection remain unclear. Fresh peripheral blood mononuclear cells (PBMCs) were collected from people living with HIV (PLWH) and HIV negative controls (NC) subjects. Soluble ligand expression levels of CD47 were measured using ELISA. HIV viral proteins or Toll-like receptor 7/8 (TLR7/8) agonist was used to investigate the mechanisms underlying the upregulation of CD47 expression. The effect of CD47 on NK cell activation, proliferation, and function were evaluated by flow cytometry. RNA-seq was used to identify downstream pathways for CD47 and its ligand interactions. A small molecule inhibitor was used to restore the inhibition of NK cell function by CD47 signalling. CD47 expression was highly upregulated on the NK cells from PLWH, which could be due to activation of the Toll-like receptor 7/8 (TLR7/8) pathway. Compared with NC subjects, PLWH subjects exhibited elevated levels of CD47 ligands, thrombospondin-1 (TSP1), and counter ligand signal regulatory protein-α (SIRPα). The TSP1-CD47 axis drives the suppression of interferon gamma (IFN-γ) production and the activation of the Janus kinase signal transducer and activator of transcription (JAK-STAT) pathway in NK cells. After treatment with a STAT3 inhibitor, the NK cells from PLWH showed significantly improved IFN-γ production. The current data indicate that the binding of the inhibitory receptor CD47 to plasma TSP1 suppresses NK cell IFN-γ production by activating the JAK/STAT3 pathway during HIV infection. Our results suggest that CD47 and its related signalling pathways could be targets for improving NK cell function in people living with HIV.